Physcoactive Substance Among High School Students in Elazig Province - Tokdemir, Mehmet; Aksu, Atınç; Baransel, Aysun (Fırat University, 2003)
Aim: Likewise in most developed countries use of psychoactive substances and dependence to these substances has became an important problem in our country. Ease of obtaining these substances, inefficiency of legal regulations, lack of education, and problems of adolescence period has important roles in gradual incline of this problem. Material and method: High school students attending to the schools in Elazig city center in 2000-2001 educational calendar were involved in this study to determine the rate of psychoactive substances in youngsters. Schools which presenting best example of the total number of students in city were selected by considering socio-culturel and economical aspects and the questionnaire was performed on a total of 1100 cases. Results: Among the most commonly used psychoactive substances thinner-baly (26.7%) and marihuanna (24.0%) while 6.8% of the participants (n=75) reported trial of psychoactive substances other than alcohol at least once in life period. It was determined that the 50.7% of the students were obtained these substance from school or street friends, and the rate of psychoactive agent use were higher in students from splittied families, families with partner problems and those with poor school performances. Conclusion: Epidemiological studies are very important for establishment of epidemiological data among substance abusers of our country. Data from the performed epidemiological studies would provide clue for establishing reason-result correlation, and provide guidance for implementations of cautions and legal regulation as well as educational programmes.

Amaç: Gelişmiş birçok ülkede olduğu gibi gelişmekte olan ülkemizde de gençler arasında psikoaktif madde kullanımının artması ve bu maddelere karşı bağımlılık önemli bir sorun halini almıştır. Bu sorunun giderek büyümesinde psikoaktif maddelere ulaşmanın kolay olması, yasal yaptırımlardaki yetersizlik, eğitim eksikliği ve ergenlik çağı sorunlarının büyük rolü vardır. Gereç ve yöntem: Gençler arasında psikoaktif madde kullanım yaygınlığını ve nedenlerini belirlemek için çalışmaya Elazığ il merkezindeki 2000-2001 eğitim öğretim yılı lise öğrencileri alınmıştır. İl genelindeki okul öğrenci sayıları, sosyo-kültürel ve ekonomik yönden dikkate alınarak her kesimi eşit temsil edecek sayıda ve özellikte okullar seçilmeye gayret edilmiş, toplam 1100 olgu üzerinde anket yapılmıştır. Bulgular: Ankete katılan öğrencilerin en fazla tiner-baly (%26.7) ve esrar (%24.0) olmak üzere %6.8'inin (n:75) hayatları boyunca bir kere de olsa alkol hariç çeşitli psikoaktif madde kullandıkları belirlenmiştir. Bu maddeleri öğrencilerin %50.7'sinin okul yada sokak arkadaşından temin ettiği, parçalanmış ailelerde, aile içi huzursuzluk yaşayanlarda ve okul başarısı zayıf gençlerde psikoaktif madde kullanımın yüksek oranda olduğu tespit edilmiştir. Sonuç: Ülkemizde madde kullanıcıları ile ilgili epidemiolojik verilerin ortaya konulması için bilimsel çalışmalar yapılması hayati önem arz etmektedir. Yapılacak olan çalışmalar neticesinde elde edilecek olan veriler sebep-sonuç ilişkilerinin ortaya konması, alınacak tedbirler, yasal yaptırımlar ve eğitim çalışmaları açısından yol gösterici olacaktır.
Elazığ İlindeki Lise Öğrencilerinde Psikoaktif Madde Kullanımı